Kebijakan Luar Negeri Amerika Serikat Untuk Menciptakan Stabilitas Hegemoni pada Era Pasca Perang Dingin - Hasyaimi, Margi A. (Global and Policy Journal of International Relations, 2015)
ABSTRACTThe United States has a long history for its domination since the Second World War. The United States and its allies obtain a victory over japan which capitulated after a bombing of Hiroshima and Nagasaki. With all the potential, the US began showing its role as a hegemon. Its superiority continuing through the establishment of international institutions such as GATT and the Bretton woods system. The cold war marked by the presence of world competition in developing nuclear weapons and spreadingof ideology that formed to be bipolar. The cold war ended with the fall of the Soviet Union and the US appeared as a solepower. In the aftermath of the cold war, US’s ideology dominated international politics and economics. According to the hegemonic stability theory, the capacities of US’s military, economic and political have the influence to affect other countries to follow its policies. The United States even able to intervene in any conflict even without UN approva.Keywords: Hegemon, Cold War, Hegemonic Stability TheoryDOI:https://doi.org/10.33005/jgp.v3i02.1941